Word Category Conversion Revisited: The Case of Adjectives and Participles in L1 and L2 German - Opitz, Andreas; Bordag, Denisa (Frontiers in Psychology, 2020)
One of the hypotheses about mental representation of conversion (i.e. zero-derivation) claims that converted forms are a product of a costly mental process that converts a word’s category into another one when needed, i.e., depending on the syntactic context in which the word appears. The empirical evidence for the claim is based primarily on self-paced reading experiments by Stolterfoht, Gese, and Maienborn (2010) in which they explored the assumed conversion of German verbs into adjectives in two syntactic contexts with participle II. In our priming study, we show that the effects that had been attributed to the conversion process are in fact frequency effects. In addition, based on our data we argue that participle II has the same word class in both syntactic contexts, as assumed by traditional German grammars. The same pattern of frequency effects was observed for German native speakers and advanced L2 German learners.